Analisis Kesenjangan Antara Pengguna dan Penyedia Elitag - Yusrida Muflihah; Agyl Ardi Rahmadi; Jessica Angelina Gatur; Ahmad Alfianto (INFORMAL: Informatics Journal, 2023)
The Elitag service is a single point of application used by University Lecturers on August 17 1945 to provide teaching through courage to students. Elitag Services has a role in helping lecturers deliver material, conduct attendance and discussions boldly. Elitag's services have increasingly gained value since distance lectures were held during the Covid-19 pandemic. However, the provision of Elitag services cannot be separated from several problems, including: 1) there is a gap between the expectations and perceptions of Elitag service users, 2) the Service Level Agreement (SLA) for Elitag services does not yet explain service requirements regarding capacity, performance and service availability, 3 ) minimum level of service evaluation. Seeing this problem, it is necessary to carry out an error analysis among Elitag service users and Elitag service providers. This research focuses on Service Level Management (SLM) which can ensure that agreements made are in accordance with customer needs, meetings between Elitag Service users and Elitag Service providers can be minimized. Referring to ITIL, the first stage that needs to be carried out is to conduct a survey using the SERVQUAL method to determine the expectations and perceptions of service users, then review the current conditions of Elitag Service SLM based on the dimensions of the SERVQUAL method. The research results show that there is a gap between the expectations and perceptions of service users, namely that the expectations of service users are higher but not in accordance with the perceptions of service users. This is indicated by the overall average score of -0.58, with the highest gap score in the responsiveness dimension (-0.73) and the lowest gap score in the Tangibles dimension (-0.43). This score shows that there is a gap but it is not significant